2020
DOI: 10.1038/s41598-020-73482-6
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase UBR5 interacts with TTC7A and may be associated with very early onset inflammatory bowel disease

Abstract: Very early onset inflammatory bowel disease (VEOIBD) denotes children with onset of IBD before six years of age. A number of monogenic disorders are associated with VEOIBD including tetratricopeptide repeat domain 7A (TTC7A) deficiency. TTC7A-deficiency is characterized by apoptotic colitis in milder cases with severe intestinal atresia and immunodeficiency in cases with complete loss of protein. We used whole exome sequencing in a VEOIBD patient presenting with colitis characterized by colonic apoptosis and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Functional studies identified that TTC7A binds to phosphatidylinositol 4‐Kinase and that loss of TTC7A in intestinal cell lines results in reduced cellular adhesion and increased apoptosis 28 . TTC7A interacts with ubiquitin protein ligase E3 component N‐regognin5 (UBR5) and recently a patient with a UBR5 mutation with VEOIBD has been identified 29 . A high‐throughput screen of compounds identified a medication, leflunomide, which increased viability in TTC7A deficient cells and may provide hope of a therapeutic intervention in this severe disease.…”
Section: Known Monogenic Causes Of Veoibdmentioning
confidence: 99%
“…Functional studies identified that TTC7A binds to phosphatidylinositol 4‐Kinase and that loss of TTC7A in intestinal cell lines results in reduced cellular adhesion and increased apoptosis 28 . TTC7A interacts with ubiquitin protein ligase E3 component N‐regognin5 (UBR5) and recently a patient with a UBR5 mutation with VEOIBD has been identified 29 . A high‐throughput screen of compounds identified a medication, leflunomide, which increased viability in TTC7A deficient cells and may provide hope of a therapeutic intervention in this severe disease.…”
Section: Known Monogenic Causes Of Veoibdmentioning
confidence: 99%
“…For the known monogenic IBD-associated genes, we reviewed current definitive guidelines 4,16 and recent publications. 17,18 The Closest Disease-causing Gene (CDG) list was created from the 99 known monogenic IBD genes, using the online Human Gene Mutation Database CDG server (http://pec630.rockefeller. edu:8080/CDG-OMIM/).…”
Section: Variant Annotation and Feature Selectionmentioning
confidence: 99%
“…For example, HERC2 was found to be a susceptibility gene for UC ( 121 , 188 ). In addition, UBR5, which is another HECTE3 ubiquitin ligase, was reported to interact with tetratricopeptide repeat domain 7A (TTC7A) and be associated with VEOIBD ( 189 ). Meanwhile, mutations in TTC7A are a pivotal pathogenic event in VEOIBD ( 190 ).…”
Section: Ub E3 Ligases and Ibdmentioning
confidence: 99%